The Effect of an 8 Week Prescribed Exercise and Low-Carbohydrate Diet on Cardiorespiratory Fitness, Body Composition and Cardiometabolic Risk Factors in Obese Individuals: A Randomised Controlled Trial - Perissiou, Maria (Nutrients, 2020)
Background: Low-carbohydrate (LC) diets are an effective method for treating obesity and reducing cardiometabolic risk. However, exposure to LC diets is associated with reductions in muscle mass and increased osteoporosis risk in obese individuals. The combination of exercise with a LC diet appears to attenuate muscle mass loss induced by LC diets alone, and to further improve cardiometabolic profile. However, evidence to date in obese individuals is limited. We assessed the effect of LC diet in combination with supervised exercise on cardiorespiratory fitness, body composition and cardiometabolic risk factors in obese individuals. Methods: Male and female participants in the experimental (EX-LC; structured supervised exercise program + low-carbohydrate meals; n = 33; 35.3 years) and control (EX-CO; structured supervised exercise program + standard dietary advice; n = 31; 34.2 years) conditions underwent measurements of cardiorespiratory fitness (VO(2)peak), body fat, lean muscle mass (LMM), and cardiometabolic biomarkers before and after an 8 week intervention. Results: Participants in the EX-LC condition demonstrated greater improvements in VO(2)peak (p = 0.002) and fat mass index (FMI, p = 0.001) compared to the EX-CO condition. Achieving a ketogenic state (β-hydroxybutyrate, βHB ≥0.3 mmol/L) was associated with greater reductions in total body fat (p = 0.011), visceral adipose tissue (p = 0.025), FMI (p = 0.002) and C-reactive protein (CRP, p = 0.041) but also with greater reductions in LMM (p = 0.042). Conclusion: Short-term LC diet combined with prescribed exercise enhanced cardiorespiratory fitness and the cardiometabolic profile of obese individuals but was also associated with greater muscle mass loss compared to similar exercise training and standard dietary advice. The long-term effects of the LC diet should be further explored in future studies.